Historical Words in The Tajik Dialect of Koson - Husniddin Normurodov (Zien Journals, 2021)
Dialect or dialect - one of the various local forms of the vernacular or national language, which has a definite system. This system has its own laws. Therefore, the practice of teaching dialect is also a great help in learning the dialect of a place. For this purpose, this article discusses the historical words in the dialect of the Tajiks Koson and their scientific and lexical significance.
Keywords: Sheva; lexicology; dialect; market